Faculty-Led Virtual Level 1 Community Fieldwork during the COVID-19 Pandemic - Tiffany L. Benaroya; Margaret Swarbrick; Michelle Zechner; Ann A. Murphy; Meredith Cimino (Journal of Occupational Therapy Education, 2022)
Fieldwork is an integral portion of occupational therapy education that ensures students have the opportunity to develop basic competencies in real world practice settings. The national shortage of fieldwork placements, particularly in the area of mental health, in combination with the COVID-19 pandemic, have led to the adoption of increasingly innovative fieldwork models. This retrospective, qualitative study investigates occupational therapy assistant students’ experiences of completing a faculty-led (i.e. where faculty served as the primary fieldwork educator) and virtual (i.e., where services were offered in a virtual environment) Level I fieldwork with a community-based peer led behavioral health agency. Twenty-three students completed a confidential survey describing their experiences in Fall 2020. A secondary analysis of students’ responses was performed using principles of thematic analysis, which yielded results centered on four themes: knowledge, skills, attitudes, and structure. Subcategories highlighted growth across multiple areas including knowledge of occupational therapy’s role in mental health, interpersonal skills, and use of technology and other resources. Students’ preconceived notions of individuals with mental illness were challenged and many reported increased confidence in their abilities to work with these individuals. Both positive and constructive feedback were provided regarding the overall virtual fieldwork experience. The faculty-led virtual fieldwork model was viable in supporting occupational therapy assistant students’ skills to engage people with mental health and substance use challenges in a community setting. The potential use of this model is discussed in light of the anticipated increase of behavioral health problems for many across the lifespan post-COVID-19 pandemic.